Perencanaan dalam Pengembangan Wisata Sungai Kali Banger di Kelurahan Kali Baros - Alifah Fidela; Nadya Ramadhanty; Akhmad Arifin Hadi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Indonesia has a wealth of natural resources, tourism and other potential that can be developed, but rivers are often overlooked. The development of the river as a tourist area is still limited to rafting, canoeing and fishing. Tourism by going along the river using a boat or boat is still not worked seriously. Kali Banger River is one of the cleanest rivers that has not been contaminated with waste so that it is used as a source of irrigation by the people of Kali Baros Village for their rice fields. But unfortunately, the development of river tourism is still constrained in several ways, namely the pile of garbage on the side of the river road and the homeless people living in Tahura. The purpose of the "Baros Kali" River Tourism Planning Program is to introduce the concept of tourism that utilizes the condition of the Banger River and the Great Forest Park (Tahura) to the visitors. The method used is a field inventory, analysis of potential and constraints with the FGD, determining the design concept and its development, and preparing the design. The result of this plan is the condition of the river and its surroundings is still fairly good, only at some point there is a pile of garbage. In addition, there are still many homeless people who live in Tahura. Before realizing the plans that have been prepared, the community needs to work together to resolve obstacles in the development of tourist areas. Keywords: grand forest park, Kali Banger, river, tourism development